PROS AND CONS OF USING MOBILE PHONE IN PUPILS LIFE - Hamroyeva , Sabinabonu Vohid qizi; Haydarova , Marjona Zafarovna (Innovative Development in Educational Activities, 2023)
In addition to paying special attention to the protection of young people from various foreign spiritual, moral, political and religious ideas, regardless of the type of society, young people have been taught to sort information through their own logical reasoning. The creation of the mobile phone is a real revolution in technical development. But all technical progress has its downsides. For example, mobile phone is harmful to human health. This article provides information about Pros and cons of using mobile phone in pupils life.